645 Preclinical development of a novel colon-targeted therapeutic for the treatment of immune checkpoint inhibitor (ICI)-colitis. (9th November 2020) - Dizman, Nazli; Greenberg, Milton L; Newman, Andrew C; Skupsky, Jonathan; Hsu, JoAnn; Zengin, Zeynep; Salgia, Nicholas; Meza, Luis; Chawla, Neal; Salgia, Sabrina; Malhotra, Jasnoor; Pal, Sumanta
Abstract : Background: Immune Checkpoint Inhibitor (ICI) therapies have significantly improved overall survival in numerous cancers, but colitis has emerged as the most frequent dose-limiting toxicity associated with these therapies. Patients experiencing colitis side effects have to discontinue their cancer therapy to treat the colitis, which repositions life-threatening cancer. An ideal therapeutic would offer a colon-restricted approach to treating colitis side effects, while allowing patients to stay on their ICI therapy, an approach unavailable with currently approved therapies. Methods: To test this localized approach for the treatment of ICI-mediated colitis, we have developed a new chemical entity as a next-generation candidate therapeutic designed for oral administration. Permeability was tested in predictive epithelial monolayers and confirmed in rodent pharmacokinetic studies. We tested the drug in the preclinical adoptive transfer model for colitis. In this model, immunodeficient mice are hosts for adoptive transfer of naïve CD4+ T cells. In the absence of regulatory T cells, the transferred cells drive systemic inflammation and migrate to the colon, causing disease. Without treatment, these mice develop signs of colitis including weight loss, altered crypt architecture and infiltration of the lamina propria by week four. Furthermore, we developed a live biopsy culture system to test drug effects on ICI-colitis patient biopsies obtained via colonoscopy. Results: In-vitro studies demonstrate that the drug has minimal toxicity and that it potently suppresses T cell proliferation and cytokine secretion. Permeability studies show a limited ability to cross the colonic mucosa restricting anti-inflammatory effects to sites of ulceration and active colitis. When colitis mice were given drug by oral gavage after colitis had developed, treated mice showed a significant increase in weight over controls and improved histological scores. Importantly, markers of systemic inflammation remained unchained, and the cancer-killing ability of the primary ICI therapy was preserved. Results of the live biopsy culture studies will be presented. Conclusions: These preliminary studies demonstrate that the candidate therapeutic has potential to become a novel next-generation oral therapy for ICI-colitis because it effectively limits leukocyte function in-vitro and in-vivo with minimal systemic absorption and minimal expected side effects. Given the favorable drug profile and the rapid growth of ICI therapies, our colon-restricted colitis therapeutic has the potential to improve outcomes in a large number of cancer patients. We anticipate commencing first-in-human studies in Q4 of 2021. Acknowledgements: None Ethics Approval: The study was approved by City of Hope Cancer Center Institutional Review Board with the approval number of 19304.